An Analysis of the Mechanical Behavior of AISI 4130 Steel after TIG and Laser Welding Process. (2015) - Neto, F. Souza; Neves, D.; Silva, O.M.M.; Lima, M.S.F.; Abdalla, A.J.
Abstract: Metallic materials have received special attention in the aerospace and defense areas. A few decades ago, Brazil was faced with technological challenges concerning the production and processing of ultra-high strength steels, such as AISI 4340 and SAE 300 M steels. The AISI 4130 steel had been also considered, since it is applied in landing gears, small aircrafts engine cradles, and besides general industries. In this work, as a comparative welding process, Laser Beam Welding (LBW) was used as an alternative to the traditional TIG (Tungsten Inert Gas) welding. For the mechanical characterization of laser and TIG welds, tensile and hardness tests were performed. Microstructural characterization through optical microscopy was realized as well, in the fusion zone (FZ) and heat-affected zone (HAZ). Martensite was found in the fusion zone for both processes. However the average grain sizes were different due to different heating and cooling rates. In the present study, the weld was autogenous and a post weld heat treatment was conducted to evaluate its influence on mechanical properties. This treatment proved to improve the ductility of the steel and reducing the embrittlement in the welded region. It was observed that the thicknesses of the FZ and HAZ in the TIG welds were ten times larger than in the laser. The hardness values observed in FZ and HAZ were similar in both cases. Tensile strength after heat treatment remained at levels similar to the base material. After the heat treatment, there was a recover in the material ductility, particularly after the laser welding, demonstrating the usefulness of the process.